2022
DOI: 10.1007/s40121-022-00649-1
|View full text |Cite
|
Sign up to set email alerts
|

Drug Resistance and Risk Factors for Acquisition of Gram-Negative Bacteria and Carbapenem-Resistant Organisms Among Liver Transplant Recipients

Abstract: Introduction: Infections caused by Gram-negative bacteria, in particular carbapenem-resistant organisms (CRO), pose a great threat to liver transplant (LT) recipients. Understanding the risk factors for Gram-negative and CRO infections and the drug resistance of corresponding bacteria will help guide the prevention and treatment of these infections.Methods: Data on the composition, distribution and drug resistance of Gram-negative bacteria and CRO among LT recipients were collected. The risk factors for Gram-n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 40 publications
0
4
0
1
Order By: Relevance
“…This increment was mostly due to the emergence of ESBLE. ESBLE is a major concern as one-year survival post-LT rates were lower than patients with non-MDRO infections [ 40 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…This increment was mostly due to the emergence of ESBLE. ESBLE is a major concern as one-year survival post-LT rates were lower than patients with non-MDRO infections [ 40 , 41 , 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that Gram-negative infections have a major role during the early post-OLT period, with pneumonia, bacteremia, and intrabdominal infections being the most frequent ones [1,[4][5][6][7][8][9][10][11]20,21]. In this scenario, beta-lactams are first-line treatments [12], and attaining an optimal PK/PD target early may allow for the maximization of clinical efficacy and suppress resistance development with beta-lactams [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, recent studies have reported that the infection rate after DCD OLT was remarkable, involving approximatively 70% of cases [3]. Bloodstream infections (BSIs) and ventilator-associated pneumonia (VAP) caused by Gram-negative pathogens represent the most frequent types of infection in early post-OLT surgery during intensive care unit (ICU) stays [4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…В 6 из 14 летальных исходов от сепсиса возбудителем была полирезистентная K. pneumoniae [7]. В спектре основных патогенов до 2013 г. преобладали E. coli и P. aeruginosa, затем их сменила полирезистентная K. pneumoniae, часто в сочетании с инвазивным кандидозом [8][9][10]. После ретрансплантации частота тяжелых осложнений и госпитальная летальность были больше, чем после первичной ОТП [11].…”
Section: материал и методыunclassified